Development of digital management - V. Ya. Tsvetkov (E-Management)
The use of digital methods and digital technologies (hereinafter referred to as DT) is a characteristic feature of the development of modern society. There are different DT: digital business, digital railway, digital management, digital photography, digital modelling, digital mapping, etc. Thus, we need to generalise and systematise them. This is partly motivated by the incorrect designation of some digital processes and technologies. First of all, it is necessary to analyse the concepts of digitalisation, digitalisation, and digital transformation. In many publications in the Russian Federation and abroad, they are considered as synonymous, close concepts. However, there is a qualitative difference between them. The DT are the general category for the listed concepts. They are the core of modern digital management. This study shows that in essence, the digitisation, digitalisation, and digital transformation are the basis of digital business and digital management. However, the concepts of digitisation, digitalastion, and digital transformation are often used interchangeably. This misconception is typical for some domestic works that use a robot translator. Often the terms “digitisation” and “digitalisation” are translated by the same word “digitalisation”, which is a linguistic error. A comparative analysis of these concepts and technologies is conducted. The difference between them is shown. Another study of the DT is conducted. The DT in many cases do not meet the requirements of conventional legal regulation and need special regulation within the framework of digital law. The conventional regulation does not consider concepts, and entities of cyber, Internet and information space and other new concepts. These new entities are considered by the digital law. The digital law is a new direction which is mandatory when using the DT and digital management.